IMPLEMENTASI PENDIDIKAN INKLUSI MELALUI STRATEGI PENGELOLAAN KELAS YANG INKLUSI PADA GURU TAMAN KANAK-KANAK DI KECAMATAN NGALIAN, SEMARANG - Adiarti, Wulan (Universitas Negeri Semarang, 2014)
Inclusive education is currently a major concern of government due to the increasing number of special needs children in Indonesia. In fact, managing a classroom with inclusion system is not easy to implement. Until now, the problems often faced by schools to implement inclusion is the readiness of teachers to manage teaching and learning activities. Based on the data obtained from the District Education Office and the Central Bureau of Statistics Ngalian Semarang ( BPS and Planning Office , 2011: 204-207 ) the number of kindergarten in District Ngalian today is as many as 46 kindergarten . Most of the institutions category that needs a lot of development, there is no institusion ready to implement inclusion . The community services activities aimed to increase knowledge of kindergarten teachers in implementing inclusive education through inclusion classroom management. Workshops and mentoring activities are carried out in this devotion, was success and smoothly, the participants began to try to implement classroom management inclusion in their institution.